2017
DOI: 10.1186/s13049-017-0451-4
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital prognosis is difficult in patients with acute exacerbation of chronic obstructive pulmonary disease

Abstract: BackgroundPatients with acute exacerbation of chronic obstructive pulmonary disease often require prehospital emergency treatment. This enables patients who are less ill to be treated on-site and to avoid hospital admission, while severely ill patients can receive immediate ventilatory support in the form of intubation. The emergency physician faces difficult treatment decisions, however, and prognostic tools that could assist in determining which patients would benefit from intubation and ventilator support w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…General home care of patients with COPD is already an established possibility in some countries [ 22 ]. It has further been reported that the majority of acute COPD patients receiving care in the EDs are discharged within 24 h of the admission [ 6 , 7 ]. A logical notion thus could be that patients with acute exacerbations of COPD also to some extent could be treated in their homes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…General home care of patients with COPD is already an established possibility in some countries [ 22 ]. It has further been reported that the majority of acute COPD patients receiving care in the EDs are discharged within 24 h of the admission [ 6 , 7 ]. A logical notion thus could be that patients with acute exacerbations of COPD also to some extent could be treated in their homes.…”
Section: Discussionmentioning
confidence: 99%
“…Although previously diagnosed with COPD, a large proportion of the patients initially screened had called the emergency medical services for complaints that could not solely be attributed to an exacerbation of COPD. Previously, we have shown that the prehospital clinical characteristics of COPD patients does not allow for prognostication as patients with COPD constitute a very disperse group [ 7 ]. As our study clearly shows, there are thus limitations to the level of ambitions regarding treat-and-release of patients solely suffering from COPD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Age, medical history, abnormal vital signs, electrocardiography (ECG) findings, pain symptoms, and the delay between symptom onset and call time are important factors for early risk assessment during the prehospital evaluation of a patient whose main complaint is dyspnea. [ 8 ] It is difficult to determine prognostic markers for mortality in patients with suspected COPD exacerbation in the prehospital setting. It has been reported that on-site treatment may be sufficient in 10% of patients with exacerbation and 30% of the patients brought to the hospital are discharged within 24 h, but mechanical ventilation is required in 6% of the patients, and the 30-day mortality is 30%.…”
Section: Prehospital Medical Care For Chronic Obstructive Pulmonary Disease Exacerbationsmentioning
confidence: 99%
“…Often the patients are treated for their exacerbation at the ED with bronchodilators, corticosteroids, and if appropriate also antibiotics [ 5 , 7 ]. If other comorbidities are excluded and the patient responds to the initial treatment, the patient will typically be discharged after a short evaluation within 24 h of admission [ 8 ]. This transport and assessment at the hospital may be inconvenient for the patients’ and relatives’ life quality, wellbeing, and pose a risk for nosocomial infection.…”
Section: Introductionmentioning
confidence: 99%